Wspomaganie procesu kompostowania kondycjonowanymi odciekami kompostowymi = Composting process power conditioning leachate compost - Bień, January; Okwiet, Tomasz; Gałwa-Widera, Monika; Worwąg, Małgorzata; Milczarek, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper attempts composting of sewage sludge in mixtures with bulking agent and green waste. The process was conducted in four experiments (one control experiment), improved by adding compost leachate. Leachate was improved by ultrasonic field with a frequency of 22 kHz and an amplitude of 12?m at the time of 5 and 15 sec.
Keywords: kompostowanie; osady ściekowe; biomasa; sewage sludge; composting; biomass